Reconciling Ethnic Differences in Nigeria through Literature education: Implications for Peace and Security (2016)
Nigeria is a country united in diversity. It is composed of diverse ethnic nationalities all trying to assert their cultural identities. The social and political developments of recent years have succeeded in creating a big hiatus in the relationship among the various nationalities. This is manifested in the spates of altercations that have been witnessed among various ethnic groups in recent times. In the face of this dwindling unity, myriads of measures put in place by the government could not achieve much. The ignorance of another culture creates fear, distrust, animosity and a disconnection between cultures in today's society. As always, to be educated about a culture different from one's own is the key to combatting this ignorance, bridge the gap and erase the fear and disconnection in order to start the reconciliation process It is, therefore, believed that using the option of literature education could bridge cultural gaps among the ethnic groups and thereby reduce conflicts to its barest minimum Exposing students to literary works from different ethnic cultures has the ability to nurture respect, empathy and acceptance among all groups. The paper also highlights the implications of this for peace and security in Nigeria